Entropy Stable Scheme on Two-Dimensional Unstructured Grids for Euler Equations (Communications in Computational Physics, 2020)
We propose an entropy stable high-resolution finite volume scheme to approximatesystems of two-dimensional symmetrizable conservation laws on unstructuredgrids. In particular we consider Euler equations governing compressible flows.The scheme is constructed using a combination of entropy conservative fluxes andentropy-stable numerical dissipation operators. High resolution is achieved based ona linear reconstruction procedure satisfying a suitable sign property that helps to maintainentropy stability. The proposed scheme is demonstrated to robustly approximatecomplex flow features by a series of benchmark numerical experiments.